Rituximab in Autoimmune CNS Disease - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at University of Sydney, Australia, and 14 international centers assessed the utility and safety of rituximab in 144 children (median age 8 years, range 0.7-17; 103 female) with autoimmune and inflammatory disorders of the CNS.